2012
DOI: 10.3892/or.2012.2012
|View full text |Cite
|
Sign up to set email alerts
|

Expression of endothelial cell-specific molecule-1 regulated by hypoxia inducible factor-1α in human colon carcinoma: Impact of ESM-1 on prognosis and its correlation with clinicopathological features

Abstract: Based on a previous finding that endothelial cell-specific molecule-1 (ESM-1) is a potential serum marker for colorectal cancer (CRC), the aim of this study was to clarify the clinicopathological significance of ESM-1 expression in CRC, and to explore the correlation between ESM-1 and HIF-1α in the tumorigenesis of CRC related to hypoxic conditions. ESM-1 mRNA expression was examined in CRC and corresponding normal mucosal tissues by reverse transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 47 publications
3
37
0
Order By: Relevance
“…Recent studies have shown that endocan is overexpressed at the mRNA and/or protein levels in various tumor types, including glioblastoma, pituitary adenoma, non-small cell lung cancer, gastric cancer, colorectal cancer, renal cell cancer, bladder cancer, ovarian cancer, and HCC 9, 12-23. Moreover, endocan overexpression in cancer tissues and sera has been associated with tumor progression and poor outcomes 13-17, 19-23. A study of the association between endocan expression and HCC patient outcomes found that microvessel density in surgically resected tumors, represented by endocan expression, was prognostic for worse survival 21.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that endocan is overexpressed at the mRNA and/or protein levels in various tumor types, including glioblastoma, pituitary adenoma, non-small cell lung cancer, gastric cancer, colorectal cancer, renal cell cancer, bladder cancer, ovarian cancer, and HCC 9, 12-23. Moreover, endocan overexpression in cancer tissues and sera has been associated with tumor progression and poor outcomes 13-17, 19-23. A study of the association between endocan expression and HCC patient outcomes found that microvessel density in surgically resected tumors, represented by endocan expression, was prognostic for worse survival 21.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing experimental evidence has reported that endocan is overexpressed in cancer, sepsis, obesity, or inflammatory conditions 6 and is related to patients' outcome in different conditions such as sepsis 7 and cancer. [8][9][10] endocan may have roles in the vascular contribution to organ-specific inflammation and in endothelium-dependent pathological disorders and may represent a novel endothelial cell dysfunction marker. 7,11 The aim of this study was threefold: (a) to evaluate endocan levels in CKD (vs. non-CKD) patients and their relation with GFR; (b) to investigate the relationship between endocan and different markers of inflammation and endothelial dysfunction in the same CKD population; and (c) to test the ability of endocan as a novel predictor of all-cause mortality and cardiovascular events (CVE) in CKD patients.…”
mentioning
confidence: 99%
“…Finally, to confirm that cardiac injury and collagen deposition were secondary to S. pneumoniae invasion, we explored the HIF1-α pathway that is activated by hypoxia (34).…”
Section: Cardiac Fibrosismentioning
confidence: 99%